Baseline CD3+CD56+ (NKT-like) Cells and the Outcome of Influenza Vaccination in Children Undergoing Chemotherapy - Leibinger, Evelin A.; Pauler, Gábor; Benedek, Noémi; Berki, Tímea; Jankovics, István; McNally, Richard; Ottóffy, Gábor (Frontiers in Immunology, 2021)
BACKGROUND In children undergoing chemotherapy yearly influenza vaccination is recommended by treatment protocols. We investigated the relationship between cellular immunity and the antibody response to inactivated influenza vaccines. METHODS 25 patients (age: 2-18 years) undergoing chemotherapy for different malignancies participated in our study. Flow cytometric detection of peripheral blood lymphocyte subpopulations together with hemagglutination inhibition antibody titers were measured before and 21-28 days after vaccination. We examined the ratio and total numbers of CD3+, CD4+, CD8+ T cells, activated helper (CD3+CD4+CD25low), regulatory (CD3+CD4+CD25high), naive (CD3+/CD45RA+) and memory (CD3+CD45RO+) T cells, CD56+NK, and CD3+CD56+ (NKT-like) cells. Relationships between specific antibody responses (seroprotection, seroconversion, geometric mean titer (GMT), geometric mean fold increase (GMFI)) and the ratios and counts of lymphocyte subpopulations were evaluated using one-way ANOVA and the paired sample t test after dichotomization according to age-related reference values. RESULTS Patients with CD4+ lymphocyte levels in the normal age-specific range showed significantly better response regarding postvaccination GMT elevation for H1N1 and H3N2 strains (97.52 vs. 19.2, p=0.019, 80 vs. 14.43, p=0.021, respectively). GMFI results were significant only against B strain (2.69-fold vs. 1.23-fold, p=0.046). Prevaccination CD3+CD56+ (NKT-like) cells above predicted values according to age showed significant associations both in postvaccination GMT elevation (H1N1: 75.11 vs. 14.14, p=0.010; H3N2: 62.18 vs. 11.22, p=0.012; B: 22.69 vs. 6.67, p=0.043) and GMFI against all three strains (H1N1: 3.76-fold vs. 1.06-fold, p=0.015; H3N2: 2.74-fold vs. 1, p=0.013; B: 2.57-fold vs. 1, p=0.008). By one-way ANOVA, we found a positive relation between absolute lymphocyte cell count above 1000/µl and the postvaccination GMT elevation against H3N2 (12.8 vs. 56.5, p=0.032), and GMFI regarding H1N1 (1.22-fold vs. 3.48-fold, p=0.044). CONCLUSIONS In addition to verifying the predictive value of absolute lymphocyte count above 1000/µl, our results suggest an association between NKT-like cell counts and the specific antibody response against all three investigated influenza strains in highly immunosuppressed patients. Furthermore, prevaccination CD4+ lymphocyte levels in the normal age-specific range may influence seroresponse.